Finnish primary care leaders' perceptions of leadership in digital health services: an inductive content analysis. (4th January 2023) - Laukka, Elina; Pölkki, Tarja; Heponiemi, Tarja; Kanste, Outi
The role of leadership in how digital health services are managed has not been extensively covered. Most of the research concerning leadership in digital services has concentrated on digital service implementation, which represents only one element of leadership. Thus, further research is needed to provide a comprehensive description of leadership in digital services. This study aimed to describe primary care leaders' perceptions of leadership in digital health services. A descriptive qualitative study involving 21 semi-structured interviews was conducted with Finnish primary care leaders in different leadership positions. Inductive content analysis was used to analyse the collected data. The following six main categories were formed: strategic leadership; operative leadership; transformational leadership; competence leadership; remote leadership; and leading collaboration and co-creation. The present research has shown that healthcare leaders require education that will provide adequate digital health capability to face today's complex, and constantly changing, digital healthcare environment.